Multiple Group I Introns in the Small-Subunit rDNA of Botryosphaeria dothidea: Implication for Intraspecific Genetic Diversity - Xu, Chao (Public Library of Science, 2013)
Botryosphaeria dothidea is a widespread and economically important pathogen on various fruit trees, and it often causes die-back and canker on limbs and fruit rot. In characterizing intraspecies genetic variation within this fungus, group I introns, rich in rDNA of fungi, may provide a productive region for exploration. In this research, we analysed complete small subunit (SSU) ribosomal DNA (rDNA) sequences of 37 B. dothidea strains, and found four insertions, designated Bdo.S943, Bdo.S1199-A, Bdo.S1199-B and Bdo.S1506, at three positions. Sequence analysis and structure prediction revealed that both Bdo.S943 and Bdo.S1506 belonged to subgroup IC1 of group I introns, whereas Bdo.S1199-A and Bdo.S1199-B corresponded to group IE introns. Moreover, Bdo.S1199-A was found to host an open reading frame (ORF) for encoding the homing endonuclease (HE), whereas Bdo.S1199-B, an evolutionary descendant of Bdo.S1199-A, included a degenerate HE. The above four introns were novel, and were the first group I introns observed and characterized in this species. Differential distribution of these introns revealed that all strains could be separated into four genotypes. Genotype III (no intron) and genotype IV (Bdo.S1199-B) were each found in only one strain, whereas genotype I (Bdo.S1199-A) and genotype II (Bdo.S943 and Bdo.S1506) occurred in 95% of the strains. There is a correlation between B. dothidea genotypes and hosts or geographic locations. Thus, these newly discovered group I introns can help to advance understanding of genetic differentiation within B. dothidea.